African origins of rice cultivation in the Black Atlantic (África, 2007)
The African diaspora was one of plants as well as people. Rice (Oryza glaberrima) led the diffusion of African plants and agricultural systems that shaped environment, food preferences, economies and cultural identity during the era of plantation slavery. By the eighteenth century the cereal was widely established from South Carolina to Brazil in the Americas. Grown by slaves as well as maroons, on plantations for subsistence as well as for export, rice cultivation accompanied African settlement of the Americas. This article reviews the indigenous knowledge systems that informed the cultivation of rice along the African as well as American Atlantic. With identical methods and practices, slaves from West Africa adapted a favored dietary staple to new conditions in the Americas, thereby ensuring the cereal’s enduring significance in Diaspora cuisines. In illuminating the African origins of Carolina rice beginnings, this paper aims to recover a significant narrative of the Atlantic slave trade